The Interaction Model Between Street-Level Bureaucrats and the Public in Health Service Provision at Puskesmas - Mahsyar, Abdul (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
This research aims at studying and explaining forms of coping behaviors and public respond to coping behaviors as shown by health service officers at street-level bureaucrats in Puskesmas (Public Health Center). The research was conducted in six Public Health Centers in Makassar, employing qualitative approach and naturalistic method. The data were gained from informants, i.e. Puskesmas officers and public patients visiting the Puskesmas as the primary data source, and the secondary data were gathered from documents available in the concerned institutions. Research data were collected through in-depth interviews, direct and participative observations. The research data were then analyzed qualitatively through data reduction, data presentation, deduction and data verification. The results of the research show variety of interactive models as a form of coping behaviors performed by bureaucrats in providing health service, namely the behavior of limiting services, rationing services, giving special treatment, ignoring, and prioritizing. The performed coping behaviors benefit the officers since their obligations were accomplished, though at minimum level. Public responds to coping behaviors quite vary but in general shows positive responds.